Design and synthesis of novel 1,2,3-triazole-dithiocarbamate hybrids as potential anticancer agents - Duan, Ying-Chao; Ma, Yong-Cheng; Zhang, En; Shi, Xiao-Jing; Wang, Meng-Meng; Ye, Xian-Wei; Liu, Hong-Min (European journal of medicinal chemistry, 2013)
A series of novel 1,2,3-triazole-dithiocarbamate hybrids were designed, synthesized and evaluated for anticancer activity against four selected human tumor cell lines (MGC-803, MCF-7, PC-3, EC-109). Majority of the synthesized compounds exhibited moderate to potent activity against MGC-803 and MCF-7. Among them, compounds 3a and 3c showed excellent broad spectrum anticancer activity with IC50 values ranging from 0.73 to 11.61 mu M and 0.49-12.45 mu M, respectively. Particularly, compound 3a was more potent than 5-fluorouracil against all tested human cancer cell lines. Flow cytometry analysis demonstrated that treatment of MGC-803 with 3c led to cell cycle arrest at G2/M phase accompanied by an increase in apoptotic cell death after 12 h. (C) 2013 Elsevier Masson SAS. All rights reserved.